Propriedades eletrônicas e estruturais de defeitos topológicos e fronteiras de grão em grafeno - Joice da Silva Araujo (2007)
In this work, we investigate electronic and structural properties of grain boundaries in graphene, with first principles calculations, based on the Kohn-Sham density functional theory, within the pseudopotential approximation. The grain boundary is formed by a periodic pattern of pentagon-heptagon pairs, and was observed, via scanning tunnelingmicroscopy, on a surface of HOPG graphite, in 2002. In our calculations, we observe various resonance peaks, introduced by the graind boundary,in the density of states of graphene, in the neighborhood of the Fermi level. The grain boundary does not induce quasi-localized resonant states at the Fermi level. In order to investigate the origin of these resonance peaks, we computed the density of states of theso-called Stone-Wales defects, formed by two adjacent pairs of fivefold-sevenfold rings. The Stone-Wales defect in its dissociated form, with two separated pentagon-heptagon pairs, was also addressed. These dissociated forms are the basic structural unit of thegrain boundary. We observe a rich structure of resonant peaks in the density of states of these defects, similar to what is observed for the grain boundary. We also considered the energetics, electronic and magnetic properties of a vacancy in the bulk of graphene and in three different sites along the grain boundary. We observe that vacancies have lower formation energies at the boundaries than in the bulk, and form spin-polarized magnetic states with moments which are slightly smaller than those obtained for bulk vacancies.